Modified Sternocleidomastoid Sparing Approach for Vertebral Artery (V1) to Common Carotid Artery Transposition: 2-Dimensional Operative Video. Issue 6 (20th February 2021) - Travers, Sarah; Siddiq, Farhan
Abstract: Vertebral artery (VA) V1 segment to common carotid artery (CCA) transposition is an uncommon operation with existing literature describing dissection of the sternoclavicular head of the sternocleidomastoid (SCM) muscle. 1, 2 We present a modified approach for transposition without cutting the SCM. Our patient is a 76-yr-old female with history of a previous cerebellar stroke. Despite taking aspirin, she presented with another stroke resulting in severe dysarthria, vertigo, and gait disturbance. Magnetic resonance imaging (MRI) demonstrated several cerebellar infarcts. Catheter angiography demonstrated bilateral vertebral artery occlusion with filling from ascending cervical branches and a dominant left VA. We planned a left V1 to CCA transposition with a modified SCM-sparing approach for which the patient provided written informed consent. She was positioned supine with neck extended and face turned to the right. Neuromonitoring was utilized. A linear incision along the anterior border of the SCM was made, stopping 1.5 cm above the clavicular head. Neurovascular structures of the carotid sheath were dissected circumferentially and mobilized medially. The longus coli muscle over the C6 lateral mass was reflected medially. The vertebral artery was dissected to expose the maximum possible length. The inferior thyroid artery was sacrificed for better exposure. VA was ligated and transected. CCA was clamped. VA to CCA bypass was performed in a standard fashion. Surgical site was closed. The patient clinically did well postoperatively with immediate symptom improvement. Our video demonstrates an SCM-sparing technique of V1 to CCA transposition, which can be a less-extensive operation compared to the traditional approaches, which require transection of SCM head.